Increase in Fluid Extraction in the Field at the Final Stage of Development - Rubel, Victoriia; Petruniak, Maryna; Mykhailovska, Olena (International Journal of Engineering and Technology, 2018)
It has been established that the fluid reserves, which are at the final stage of development, are difficult to extracta and water. The methods of intensification are analyzed and it is established that it will be rational in this case to pump carbon dioxide into the reservoir. Its influence on a bundle of oil and water is determined. The results of the statistical processing of the change of the debit before and after injection of carbon dioxide, the influence of the volume of gas injected into the well from the seperate permeability of the reservoir, as well as the expected rate of wellbore after injection, are presented.